2020
DOI: 10.1111/bcp.14185
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib, sunitinib and pazopanib: From flat‐fixed dosing towards a pharmacokinetically guided personalized dose

Abstract: Tyrosine kinase inhibitors (TKIs) are anti‐cancer drugs that target tyrosine kinases, enzymes that are involved in multiple cellular processes. Currently, multiple oral TKIs have been introduced in the treatment of solid tumours, all administered in a fixed dose, although large interpatient pharmacokinetic (PK) variability is described. For imatinib, sunitinib and pazopanib exposure‐treatment outcome (efficacy and toxicity) relationships have been established and therapeutic windows have been defined, therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 140 publications
(350 reference statements)
2
71
1
Order By: Relevance
“…This applies in particular for imatinib, sunitinib and pazopanib, in which therapeutic windows have been defined and the feasibility of TDM to reach drug levels within these therapeutic windows has been shown 14–18 . Therefore, TDM‐guided dosing is considered viable for these three drugs and is currently being implemented as a standard of care in the Netherlands 12,19 …”
Section: Introductionmentioning
confidence: 99%
“…This applies in particular for imatinib, sunitinib and pazopanib, in which therapeutic windows have been defined and the feasibility of TDM to reach drug levels within these therapeutic windows has been shown 14–18 . Therefore, TDM‐guided dosing is considered viable for these three drugs and is currently being implemented as a standard of care in the Netherlands 12,19 …”
Section: Introductionmentioning
confidence: 99%
“…The blood concentration of IM reached the peak after 1.8-4.0 hours (Cmax), 16 but it will take 6-12 hours for SU to reach the Cmax. 17 However, the important monitoring index that can reflect the therapeutic effect is based on the steady-state blood trough concentration (Cmin) level of IM or SU, and Cmin is relatively stable and easier to be monitored. Demetri et al found that 18 the GIST patients who used IM and obtained steady-state Cmin were divided into quartiles, and the Cmin was higher than the lowest quartile of 1100ng/mL, their disease was effectively controlled.…”
Section: Opportunity For Monitoring the Blood Concentration Of Tkismentioning
confidence: 99%
“…Once drug exposure–response studies successfully define a target therapeutic concentration range or efficacy cut‐off, prospective dose‐adjustment trials intended to demonstrate that TDM can be implemented should be initiated (Figure 1, Stage 3). The primary outcome of this type of study is the proportion of patients starting the treatment under‐ or over‐exposed who successfully achieve therapeutic blood drug levels following recommendations for dose adjustments 2–6,37–40 . Such TDM feasibility studies may compare the prevalence of therapeutic exposure before and after dose adjustment recommendation in the same group of subjects or, preferably, with a separate control arm.…”
Section: Evaluating the Feasibility Of Tdmmentioning
confidence: 99%
“…As mentioned above, numerous examples of such studies evaluating feasibility of TDM for oral small molecule anticancer drugs are available and many of them indeed succeed in increasing the proportion of patients with drug levels in the therapeutic range 2–6,37–40 . An example that deserves special mention is the recently described study of the Dutch Pharmacology Oncology Group 38 .…”
Section: Evaluating the Feasibility Of Tdmmentioning
confidence: 99%